STORYTELLING DALAM FILM SUZZANNA MALAM JUMAT KLIWON: ANALISIS PERBANDINGAN VERSI 1986 DENGAN VERSI 2023 - Ananda Oktafiyani; Azmi Puji Rahmawati (Journal of Innovation Research and Knowledge, 2025)
The Indonesian film industry has undergone a significant transformation in recent years, with an increase in viewership and the success of local films, including in the horror genre. This research addresses the comparison between two versions of Suzzanna Malam Jumat Kliwon, namely the 1986 and 2023 versions, to analyze the differences in storytelling, characters, plot, and cultural elements. Using a descriptive qualitative approach with content analysis, this study shows that although both versions have similar premises, there are notable differences in narrative structure, characters, and conflict resolution. These changes reflect a shift in Indonesian horror storytelling style, from a traditional approach towards a more modern and complex narrative exploration. This study provides insight into how the development of the horror genre in Indonesia is influenced by changing audience tastes and the broader socio-cultural context.